2022
DOI: 10.3389/fonc.2022.818314
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Plasmacytoid Dendritic Cells in Gastric Cancer

Abstract: Gastric cancer (GC) is the fifth most common neoplasm and the third most deadly cancer in humans worldwide. Helicobacter pylori infection is the most important causative factor of gastric carcinogenesis, and activates host innate and adaptive immune responses. As key constituents of the tumor immune microenvironment, plasmacytoid dendritic cells (pDCs) are increasingly attracting attention owing to their potential roles in immunosuppression. We recently reported that pDCs have vital roles in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…Although plasmacytoid DC normally exhibit robust IFN-α production following TLR-mediated activation they can lose this function with chronic activation and contribute to an immunosuppressive tumor microenvironment [ 33 ]. Indeed, they have been suggested a potential target for therapy in gastric cancer [ 34 ] and these data indicate that this may also be the case for EAC where it was also noteworthy that they were highly sensitive to chemotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…Although plasmacytoid DC normally exhibit robust IFN-α production following TLR-mediated activation they can lose this function with chronic activation and contribute to an immunosuppressive tumor microenvironment [ 33 ]. Indeed, they have been suggested a potential target for therapy in gastric cancer [ 34 ] and these data indicate that this may also be the case for EAC where it was also noteworthy that they were highly sensitive to chemotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…Although plasmacytoid DC normally exhibit robust IFN-α production following TLR-mediated activation they can lose this function with chronic activation and contribute to an immunosuppressive tumor microenvironment (Mitchell et al, 2018). Indeed, they have been suggested a potential target for therapy in gastric cancer (Yang et al, 2022) and these data indicate that this may also be the case for EAC where it was also noteworthy that they were highly sensitive to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial taxonomic features (MTFs) can be used to predict early gastric neoplasia (EGN; Png et al, 2022 ) and may improve the accuracy of the polygenic risk score (PRS) model in predicting GC ( Wang et al, 2023 ). As for the mechanism, many studies have revealed that non- H. pylori microorganisms promote GC by inducing inflammation, modulating the immune response, triggering DNA damage, and promoting epithelial–mesenchymal transformation ( Yang et al, 2022 ; Liao et al, 2023 ). Gastric non- H. pylori microorganisms may participate in the progression of GC by affecting host DNA methylation ( Yue et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%